Effectiveness of modified biochar–humic acid–microbe–based granular organic fertilizer on mung bean in calcareous soil - Matheus, Rupa; Kantur, Donatus; Pallo, Marchy; Risbarkah, Euis Bayu (Brawijaya University, 2026)
Calcareous soil is one of the dominant and potentially productive soil types found on Timor Island; however, it faces a major constraint in agricultural production due to relatively low nutrient availability, particularly phosphorus. This condition reduces the efficiency of chemical fertilizer application. Therefore, this study was conducted to evaluate the effectiveness of organic granular fertilizer based on modified biochar, humic acid, and functional microbes on the uptake of nitrogen (N) and phosphorus (P), as well as on the growth and yield of mung bean (Vigna radiata L.) cultivated in calcareous soils. An explanatory pot experiment was conducted in the Screen House of the State Agricultural Polytechnic of Kupang, employing a completely randomized design with several types of organic granular fertilizer (F1-F4) and a control (P0), each replicated three times. Compared with the control, the F4 treatment consistently produced the most favorable responses, including greater plant growth and higher nutrient uptake. Furthermore, the application of the F4 fertilizer formula simultaneously improved soil chemical properties, encompassing organic C content, soil N, available P, exchangeable K, and cation exchange capacity, indicating that the F4 formula has potential as an alternative for enhancing the productivity of calcareous soils.